Lithium lanthanum zirconate thin films investigated using spectroscopic and microscopic techniques - Anjali; Lim, Weon Cheol; Kim, So Hee; Sharma, Aditya; Moditma; Lee, Sangsul; Shin, Hyun-Joon; Chae, Keun Hwa; Singh, Jitendra Pal (Taylor & Francis, 2025)
In this work, thin film growth of lithium lanthanum zirconate (LLZO) on p-type Si substrate was carried out using radio frequency (RF) sputtering and was characterized using microscopic and various spectroscopic techniques including X-ray absorption spectroscopy. Films were deposited at a sputtering power of 70？W at a based pressure of 4？×？10？5 Torr. Deposited films were annealed at 700°C for 1？h. The as-deposited films were amorphous and no transition to a crystalline phase was observed after annealing. Although films are amorphous Raman spectroscopic measurements exhibit the bands that are characteristics of LLZO. The thickness of the as-deposited film estimated from Rutherford backscattering spectroscopy (RBS) was 100？nm and remained unchanged after annealing. The thickness of the annealed films as determined from scanning electron microscopy (SEM) was 48？±？21？nm. The composition of these films determined from RBS is almost analogues to that estimated from SEM-energy-dispersive spectroscopic measurements. However, O K-edge near edge X-ray absorption fine structure spectra showed slight modification with annealing but a drastic change was observed in the spectra measured in total electron yield and total fluorescence yield measurements. This change is due to the difference like the interaction of oxygen ions with its neighbouring atoms on the surface and in the bulk of the films.